iOS cloud development for dummies - Goldstein, Neal. (For Dummies., 2012)
Build robust, data-driven mobile apps and web services that take advantage of iCloud. This guide will help you create apps that share data, keep that data current, sync it with iCloud, and more-- |c Source other than Libary of Congress.